2017
DOI: 10.3389/fcimb.2017.00485
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Conserved ABC Importers Necessary for Intracellular Survival of Legionella pneumophila in Multiple Hosts

Abstract: It is established that the human pathogen Legionella pneumophila becomes significantly augmented for infection of macrophages after intracellular growth in amoebae when compared to like-strains cultivated in laboratory media. Based on this observation, we reasoned that the most critical virulence determinants of L.p. are expressed by responding to stimuli generated by the protozoan host specifically; a process we term “protozoan-priming.” We sought to identify L.p. virulence factors that were required for repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…pneumophila during post-exponential growth, most notably for the generation of the storage molecule, PHB 39 , 46 , 49 , and nutrient importers are important for intracellular growth of L . pneumophila 6 , 87 . Having large stores of PHB allows the organism to persist outside of the host for extended periods of time 51 .Transcriptomic studies in the human macrophage cell line THP-1 have demonstrated that expression of lamB is highest early in infection (8 hrs) rather than later (14 hrs), opposite of when the organism starts increasing consumption of glucose 46 , 88 .…”
Section: Discussionmentioning
confidence: 99%
“…pneumophila during post-exponential growth, most notably for the generation of the storage molecule, PHB 39 , 46 , 49 , and nutrient importers are important for intracellular growth of L . pneumophila 6 , 87 . Having large stores of PHB allows the organism to persist outside of the host for extended periods of time 51 .Transcriptomic studies in the human macrophage cell line THP-1 have demonstrated that expression of lamB is highest early in infection (8 hrs) rather than later (14 hrs), opposite of when the organism starts increasing consumption of glucose 46 , 88 .…”
Section: Discussionmentioning
confidence: 99%
“…To multiply within hosts, Lp requires a Dot/Icm type IVb secretion system to deliver more than 300 effector proteins (comprising nearly 10% of the Lp genome) directly into the host cells; this allows Lp to evade host defenses and establish replication vacuoles. , As repeated cycles of intracellular replication followed by dissemination are believed to be critical to Legionella persistence in the environment, this extensive catalogue of effector proteins is believed to reflect the diverse range of hosts that Legionella is capable of infecting. , It has been hypothesized that the interaction of Lp with environmental hosts is what led to the evolution of Lp ’s human virulence. Despite the similar strategies used by Lp for infecting FLA and human macrophage, Lp ’s increased infectivity upon egress appears to be exclusive to passage through FLA . Key human virulence factors must therefore be produced by Lp in response to stimuli within FLA, a process we have previously coined protozoan-priming . However, the specific stimuli within FLA that contribute to the increased human virulence have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Within the LCV, bacterial metabolism and nutrition-based genetic regulation based in nutrient availability governs bacterial proliferation and differentiation (W. Eisenreich, Heesemann, Rudel, & Goebel, 2013; Wolfgang Eisenreich, Rudel, Heesemann, & Goebel, 2017; Fonseca & Swanson, 2014; Grubmuller, Schauer, Goebel, Fuchs, & Eisenreich, 2014; Häuslein et al, 2017; Lama, Drennan, Johnson, Rubenstein, & Cambronne, 2017; Manske & Hilbi, 2014; Oliva, Sahr, & Buchrieser, 2018; C. T. Price, Richards, & Abu Kwaik, 2014).…”
mentioning
confidence: 99%